Kajian: Pengembangan Varietas Unggul Baru Padi (Oryza sativa L.) Lokal melalui Iridasi Gamma - Henny Puspita Sari; Irfan Suliansyah; Aswaldi Anwar; Indra Dwipa (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The widespread use of mutagenesis for plant genetic improvement can be explained by a number of factors, including the fact that new varieties can be developed in a shorter time than conventional breeding methods and that transgenesis is more difficult to re-engineer. Gamma rays are physical mutagens that are often used in plant mutagenesis techniques and are safe for human health because there is no environmental risk in the induced generations. The method used in this paper is by grouping articles according to their relevance to the subject and year of research, and finally managing the explanatory structure. Journal articles for the period 2012 to 2022 were searched using keywords: breeding, mutation, mutagen, rice, and gamma iridation. The selection of selected articles comes from the PubMed, Elsevier, and Springer web sites. This paper integrates the available data on the effects of mutation breeding of plant varieties in different countries and addresses the potential of gamma irrigation as a flexible and practical approach that can be applied to rice crops and an appropriate selection method.